2009
DOI: 10.1139/t08-120
|View full text |Cite
|
Sign up to set email alerts
|

Swelling characteristics of bentonites in artificial seawater

Abstract: Bentonite is currently designated for use as a buffer material for the repository of high-level radioactive waste because such a material requires swelling characteristics to seal the waste. A high-level radioactive waste disposal facility may be built in a coastal area of Japan because transportation of this waste by ships is feasible. Therefore, it is important to investigate the effects of seawater on a bentonite-based buffer. This study is intended to investigate the influence of seawater on the swelling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(36 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…Kunigel-V1 is a commercial sodium type bentonite from Yamagata, Japan, containing 48z to 57z montmorillonite (smectite mineral), with ratios depending on the deposit depth (Komine, 2004;Komine et al, 2009) and other non-swelling minerals, such as quartz, zeolite, and feldspar. NSF Clay is a commercially available non-swelling clay from Okayama, Japan, and is mainly composed of illite, with other minor minerals, such as quartz and feldspar.…”
Section: Materials/specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Kunigel-V1 is a commercial sodium type bentonite from Yamagata, Japan, containing 48z to 57z montmorillonite (smectite mineral), with ratios depending on the deposit depth (Komine, 2004;Komine et al, 2009) and other non-swelling minerals, such as quartz, zeolite, and feldspar. NSF Clay is a commercially available non-swelling clay from Okayama, Japan, and is mainly composed of illite, with other minor minerals, such as quartz and feldspar.…”
Section: Materials/specimensmentioning
confidence: 99%
“…There is a possibility that the strain rate employed in this investigation is not slow enough for water to move from one location to another, allowing for particle rearrangement. Komine and Ogata (1994,2004) and Komine et al (2009) have performed numerous studies to observe the swelling behaviour of Kunigel-V1. The testing methods employed required a testing period of one week, but swelling was observed within theˆrst day, meaning swelling was almost instantaneous.…”
Section: Compression Behaviourmentioning
confidence: 99%
“…Several investigations have been undertaken to evaluate the effect of wet and dry cycles combined with cation exchange on hydraulic conductivity and swelling ability of clay barriers (Hewitt and Philip, 1999;Lin and Benson, 2000;Bouazza et al, 2006Bouazza et al, , 2007Thiel et al, 2006;Komine et al, 2009;Rowe et al, 2011;Tang et al, 2011;De Camillis et al, 2014;Mukunoki et al, 2014;He et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the permeant salinity on the intrinsic permeability of the granite/bentonite mixture has been highlighted by Villar (2006), as well as the swelling capacity of this mixture. This kind of alteration of clays due to the interaction with chemical fluids has been confirmed by numerous researchers in literature and found that the swelling pressure of bentonite decreases as the salinity of pore water increases (Karnland et al, 2006;Castellanos et al, 2008;Herbert et al, 2008;Komine et al, 2009;, and the hydraulic conductivity of bentonite increases as the concentration of infiltrating solution increases (Studds et al, 1998;Mata, 2003;Villar, 2005;.…”
Section: Introductionmentioning
confidence: 67%